2021
DOI: 10.1016/j.artd.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Does the Surgical Approach Influence the Canal Fill of the Proximal Femur for Hip Arthroplasty?

Abstract: Background Choosing the right size of the stem is crucial for uncemented hip arthroplasty. Undersizing can lead to early loosening, peri-prosthetic fracture due to femoral implant insertion, and/or osteointegration failure. The main objective of this study was to find a correlation between the surgical approach and the intramedullary prosthetic canal fill ratio (CFR) of the uncemented femoral implant. The hypothesis of this work was that the surgical approach does not influence the stem sizing dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…1 study reported no influence of surgical approach on the canal fill of the proximal femur [24]. Another reported increased risk of stem undersizing with AA [25].…”
Section: Discussionmentioning
confidence: 96%
“…1 study reported no influence of surgical approach on the canal fill of the proximal femur [24]. Another reported increased risk of stem undersizing with AA [25].…”
Section: Discussionmentioning
confidence: 96%
“…The proximal femur is an anatomical structure that transitions from the wide metaphyseal region to the diaphyseal region in a narrowing shape, and it has many anatomical variations (Mattesi et al, 2021). It has been shown that the success of hip joint reconstructions is closely related to implant design and that the diameter of the nail to be used is important for the union of femur fractures (Fessy et al, 1997).…”
Section: Discussionmentioning
confidence: 99%